An Exploration of Integration Journeys, Identity, and Well-Being with Syrian Refugee Youth - Rabiah-Mohammed, Fawziah; Oudshoorn, Abe; Hussain, Yasmin (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2025)
Settlement in a new country is a complex social experience. The aim of this study is to explore via photovoice how integration is experienced and navigated in relation to family, peers/friendships, school, work, and community for Syrian refugee youth. We propose four themes through which we can understand the integration experiences of Syrian refugee youth: (a) integration as a chronological journey, (b) bridging or interweaving cultures, (d) managing exclusions, and (d) questioning the premise. Underpinning these four themes is a fifth that runs throughout: resilience in personal strength and external support. These themes provide a detailed explanation of the rhythmic process of integration and supportive factors that enhance resilience.